2016
DOI: 10.3390/ijms17060879
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Rhodiola rosea L. on Bleomycin-Induced Pulmonary Fibrosis in Rats

Abstract: Rhodiola rosea L. (RRL) possesses a wide range of pharmacological properties, including lung-protective activity, and has been utilized in folk medicine for several 100 years. However, the lung-protective mechanism remains unclear. This study investigated the possible lung-protective activity mechanism of RRL in a pulmonary fibrosis (PF) rat model. Lung fibrotic injury was induced in Sprague–Dawley rats by single intratracheal instillation of saline containing bleomycin (BLM; 5 mg/kg). The rats were administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 37 publications
(34 reference statements)
1
32
0
1
Order By: Relevance
“…The 95% ethanol extract of R. rosea (Extract 76) could alleviate fibrotic lung injury in PF rats dose-dependently (125,250, and 500 mg/kg/d). 182 HYP was reduced by R. rosea, along with increase of GSH and T-SOD. Meanwhile, the bronchoalveolar lavage fluid levels of TNF-α, TGF-β1, and IL-6 were decreased.…”
Section: Anti-inflammatory and Analgesic Activitiesmentioning
confidence: 87%
See 1 more Smart Citation
“…The 95% ethanol extract of R. rosea (Extract 76) could alleviate fibrotic lung injury in PF rats dose-dependently (125,250, and 500 mg/kg/d). 182 HYP was reduced by R. rosea, along with increase of GSH and T-SOD. Meanwhile, the bronchoalveolar lavage fluid levels of TNF-α, TGF-β1, and IL-6 were decreased.…”
Section: Anti-inflammatory and Analgesic Activitiesmentioning
confidence: 87%
“…The lung‐protective effect of R. rosea has been investigated on BLM‐induced pulmonary fibrosis (PF) rat model. The 95% ethanol extract of R. rosea (Extract 76 ) could alleviate fibrotic lung injury in PF rats dose‐dependently (125, 250, and 500 mg/kg/d) . HYP was reduced by R. rosea , along with increase of GSH and T‐SOD.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…In addition, several studies have demonstrated that bleomycin administration in rats decreased the anti-oxidative capacity and increased oxidative stress in the lung tissue, which aggravated pulmonary fibrosis. 13,14,15 It has been established that in bleomycin induced pulmonary fibrosis the levels of the biochemical, oxidant and antioxidant parameters changed significantly than those of the normal levels. This is evident by increased levels Lactate Dehydrogenase (LDH) which is a marker of biochemical index.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that anti-oxidant agents ameliorated the accumulation of leukocytes in bronchial lavage fluid and lung tissue which agrees with our findings. [12][13][14][15][16][17][18][19] The pathophysiology of Bleomycin-induced lung injury typically consisted of two overlapping stages; an early inflammatory phase characterized by leukocyte infiltration and injury to alveolar epithelial cells, and a subsequent fibro-proliferative phase with matrix remodeling and fibrosis. 20 Haematoxylin & Eosin (H&E) staining results in BLM control group showed that acute inflammations were prominent with moderate or severe hemorrhage, widened alveolar septa, and infiltration of numerous inflammatory cells predominated by macrophages, neutral granulocytes, and lymphocytes.…”
Section: Hydroxylprolinementioning
confidence: 99%
“…Por otro lado, los hallazgos histopatológicos son comparables con otros estudios que evalúan efectos potenciales de plantas medicinales. Por ejemplo, Zhang et al al evaluar el efecto antifibrótico del extracto etanólico de Rhodiola rosea L. encontraron una disminución discreta de los cambios histopatológicos mostrados y de las fibras de colágeno alrededor de los vasos pulmonares en comparación a lo mostrado por el control (inducido con bleomicina) [33] ; mientras que M. Iraz et al, encontraron que la administración de una solución acuosa de Ginkgo biloba, podía prevenir el incremento del índice de Ashcroft en los ratones a los que se les induce fibrosis con bleomicina [34] .…”
Section: Referencias Bibliográficasunclassified